ALTERNATIF SOLUSI MEMECAHKAN MASALAH MELEMAHNYA EKONOMI GLOBAL DIBAWAH KENDALI SISTEM KAPITALISME - Ade, Priangani (JURNAL KEBANGSAAN, 2017)
The struggle against the global financial crisis in the last six years did not indicate the direction of improvement. Lokomotiv countries of the world economy even threatened a new crisis. Germany in danger of recession, conjuncture in China continued to slow, and the United States increasingly overwhelmed and difficult to recover due to weak global economy. Keywords: Weakening Global Economy, Capitalism.